Diari Mingguan Pusat Kokurikulum UPSI 18-24 Sept 2023/ Edisi 189 - Pusat Kokurikulum UPSI (Tanjong Malim, 2023)
Diari Mingguan Pusat Kokurikulum UPSI 18-24 Sept 2023/ Edisi 189 by Pusat Kokurikulum UPSI